Voluntary contributions to informal activities producing public goods: can these be induced by government and other formal sector agents? Some evidence from Indonesian posyandus - Jeffrey B. Nugent; Shailender Swaminathan (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2005)
This study attempts to determine the extent to which human potential may be unlocked by government or other formal sector actions that induce voluntary contributions by individuals to the activities of Indonesia's posyandus or village health posts. Posyandus have been an important feature of Indonesia's public health system and have contributed substantially to the country's success in lowering infant and child mortality rates at low cost. Our analysis of links between formal activity and voluntary contributions to posyandus is conducted at two levels: individuals and posyandus, and with two different indicators at each level. Our empirical results take advantage of data from all three waves of the Indonesian Family Life Survey (IFLS), i.e., IFLS1, IFLS2 and IFLS3. At each level of analysis there is evidence that voluntary contributions and effective service provision can be positively affected by formal sector intervention. Both community level characteristics, such as income per capita, income inequality, ethnic and religious diversity, and household and individual characteristics have different effects on the different outcome variables at both levels of analysis. The results demonstrate that appropriately designed formal sector interventions can induce voluntary inputs and, through the public goods produced, they can unlock the human potential. – voluntarism ; Indonesia ; health service provision ; government intervention
Keywords: H42; I18; J22; O15; O17; R29; 330